The Dimension Of Religiosity In The Cleopatra Cleopatra Novel - Hartini, Tri; Andayani, Andayani; Anindyarini, Atikah (Jurnal Lektur Keagamaan, 2020)
This study aims to describe several dimensions of religiosity in Habbiburrahman El Shirazy's novel Pudarnya Pesona Cleopatra. In addition, it is also to illustrate the relevance of literary works as teaching materials in literature learning at the high school level. The method used in this study is descriptive qualitative method with content analysis techniques. The results of this study found 18 dimensions of religiosity, including 3 dimensions of belief data, 3 dimensions of worship data, 5 dimensions of experience data, 4 dimensions of religious knowledge, and 3 data dimensions of effects. The data is relevant to Indonesian literature learning related to basic competencies to find elements and features of novel language in high school level. Thus, this novel can be used as teaching material. Keywords: dimensions of religiosity, novel, learning Â  Tulisan ini bertujuan untuk mendeskripsikan beberapa dimensi religiositas dalam novel Pudarnya Pesona Cleopatra karya Habbiburrahman El Shirazy. Selain itu juga untuk menggambarkan relevansi karya sastra sebagai bahan ajar dalam pembelajaran sastra di tingkat sekolah menengah. Metode yang digunakan dalam kajian ini ialah metode deskriptif kualitatif dengan teknik analisis isi. Hasil kajian ini menemukan 18 dimensi religiositas antara lain 3 data dimensi keyakinan, 3 data dimensi peribadatan, 5 data dimensi pengalaman, 4 data dimensi pengetahuan agama, dan 3 data dimensi efek. Data tersebut relevan dengan pembelajaran sastra Indonesia terkait dengan kompetensi dasar untuk menemukan unsur dan ciri kebahasaan novel tingkat Sekolah Menengah Atas. Dengan demikian, novel ini dapat digunakan sebagai bahan ajar. Kata Kunci: dimensi religiositas, novel, pembelajaran